Latin America in Times of Turbulence Presidentialism under Stress - Llanos, Mariana; Marsteintredet, Leiv (Routledge Studies in Latin American Politics, 2023)
This book accounts for and analyses the latest developments in Latin American presidential democracies, with a special focus on political institutions. The stellar line-up of renowned scholars of Latin American politics and institutions from Latin America, Europe, and the United States offer new insights into how democratic institutions have operated within the critical context that marked the political and social life of the region in the last few years: the eruption of popular protest and discontent, the widespread distrust of political institutions, and, of course, the COVID-19 pandemic. Combining different methodological approaches, including cross-national studies, small-N studies, case studies, and quantitative and qualitative data, the contributions cluster around three themes: the problem with fixed terms and other features of presidentialism, inter-institutional relations and executive accountability, and old and new threats to democracy in these times of turmoil. The volume concludes with an assessment of the political consequences of the COVID-19 pandemic in Latin America. Beyond current scholars and students of comparative political scientists, Latin America in Times of Turbulence will be of great interest to a wide spectrum of readers interested in comparative systems of government, democracy studies, and Latin American politics more generally.